2018
DOI: 10.14735/amko20189
|View full text |Cite
|
Sign up to set email alerts
|

AR-V7 Androgen Receptor Variant as a Predictor of Response to Androgen-receptor Targeting Agents Used to Treat Castration-refractory Metastatic Prostate Cancer

Abstract: 1 Onkologická klinika 1. LF UK a Thomayerovy nemocnice, Praha 2 Ústav laboratorní dia gnostiky, FN Královské Vinohrady, Praha 3 III. chirurgická klinika 1. LF UK a FN Motol, Praha SouhrnVýchodiska: U nemocných s metastatickým kastračně refrakterním karcinomem prostaty (metastatic castration-refractory prostate cancer -mCRPC) existuje několik možností systémové léčby, zahrnující zejména enzalutamid a abirateron, souhrnně nazývané androgen-receptor target ing agents (ARTA), taxany docetaxel a cabazitaxel a radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…The results of a prospective clinical trial evaluating abiraterone in 454 patients treated in clinical practice demonstrated the median PFS 17.3 (95% CI: 14.1-19.4) months and median OS 37.3 (95% CI: 36.5 -not reached) months. There was a higher percentage of patients above 75 years old in the study and higher proportion of patients with visceral disease than in our group [22].…”
Section: Discussioncontrasting
confidence: 65%
“…The results of a prospective clinical trial evaluating abiraterone in 454 patients treated in clinical practice demonstrated the median PFS 17.3 (95% CI: 14.1-19.4) months and median OS 37.3 (95% CI: 36.5 -not reached) months. There was a higher percentage of patients above 75 years old in the study and higher proportion of patients with visceral disease than in our group [22].…”
Section: Discussioncontrasting
confidence: 65%